2017
DOI: 10.3390/nano7060139
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis of Metal Nanoparticles Using a Biosurfactant Extracted from Corn and Their Antimicrobial Properties

Abstract: A new and promising biosurfactant extracted from corn steep liquor has been used for the green synthesis of gold and silver nanoparticles (NPs) in a one-step procedure induced by temperature. Most of the biosurfactants proposed in the literature are produced by pathogenic microorganisms; whereas the biosurfactant used in the current work was extracted from a liquid stream, fermented spontaneously by lactic acid bacteria, which are “generally recognized as safe” (GRAS) microorganisms. The reduction of a gold pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Undoubtedly, continuing research in this promising direction is advisable. However, it does not lower the observations regarding the antimicrobial activity of the metal nanoparticles obtained by another synthesis route [ 8 , 9 , 35 , 40 , 43 , 45 , 53 55 ].…”
Section: Resultsmentioning
confidence: 72%
“…Undoubtedly, continuing research in this promising direction is advisable. However, it does not lower the observations regarding the antimicrobial activity of the metal nanoparticles obtained by another synthesis route [ 8 , 9 , 35 , 40 , 43 , 45 , 53 55 ].…”
Section: Resultsmentioning
confidence: 72%
“…The bands of MEL in Ag and ZnO nanoparticles were shiing remarkably, which might be due to the reduction of Ag and ZnO. 49 GA displayed notable stretching vibration bands at 3386, 2920 and 1420 cm À1 that correspond to O-H stretching vibration of polymer, C-H stretching of CH 2 group and the deformations of the CH 2 group, respectively. These results are in a good agreement with other reports.…”
Section: Characterization Of Nanocompositesmentioning
confidence: 96%
“…BS molecules can work excitingly in synergistic way (against pathogens) in association with antibiotics, NPs etc. Gómez-Graña et al [40] suggested that the CFBS exhibit deep impact in reducing the metal precursor and also stabilizing the NPs. More importantly, BS stabilizes NPs and exhibits antimicrobial activity against various pathogens like E. coli, Ps.…”
Section: Foley Catheter Assay To Evaluate Inhibition Of Bacterial Biomentioning
confidence: 99%